2012
DOI: 10.1111/j.1541-0420.2012.01767.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Adaptive Marginal Analysis of Longitudinal Neuroimaging Data with Time‐Varying Covariates

Abstract: Summary Neuroimaging data collected at repeated occasions are gaining increasing attention in the neuroimaging community due to their potential in answering questions regarding brain development, aging, and neurodegeneration. These datasets are large and complicated, characterized by the intricate spatial dependence structure of each response image, multiple response images per subject, and covariates that may vary with time. We propose a multiscale adaptive generalized method of moments (MA-GMM) approach to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…Significant group differences were found between control subjects, MCI patients who did or did not subsequently convert to AD (MCI-c and MCI-nc, respectively) and AD patients, and the authors suggested that the method may be particularly useful as an AD biomarker in conjunction with shape analysis, as both approaches leverage complementary information. Two new approaches for analyzing longitudinal MRI data sets were reported by Skup et al [380] and Bernal-Rusiel et al [381]. The multiscale adaptive generalized method of moments [380] tackles the problem of analysis of longitudinal MRI data sets that have multiple response images per subject.…”
Section: Methods Papersmentioning
confidence: 99%
“…Significant group differences were found between control subjects, MCI patients who did or did not subsequently convert to AD (MCI-c and MCI-nc, respectively) and AD patients, and the authors suggested that the method may be particularly useful as an AD biomarker in conjunction with shape analysis, as both approaches leverage complementary information. Two new approaches for analyzing longitudinal MRI data sets were reported by Skup et al [380] and Bernal-Rusiel et al [381]. The multiscale adaptive generalized method of moments [380] tackles the problem of analysis of longitudinal MRI data sets that have multiple response images per subject.…”
Section: Methods Papersmentioning
confidence: 99%
“…Although we have designed the simulation studies by assuming a single quantitative secondary trait and the additive mode of inheritance, the studies can be easily extended to consider other kind of secondary traits such as binary traits (Wang and Shete (2011); Chen et al (2013)), longitudinal traits (Skup et al (2012); Xu et al (2014)), multiple traits (Lin et al (2012); Zhang et al (2014); Zhu et al (2014)) as well as other modes of inheritance. We only include AD patients and CN subjects in the GWAS of ADNI data in the paper, but we may include the MCI subjects in our GWAS and treat them as controls by following the analysis in Kim and Pan (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is common to use Gaussian smoothing with a prefixed bandwidth, it may introduce substantial bias in the statistical results (Li et al, 2012, 2013). Although several multi-scale adaptive regression models (MARMs) have been developed for the group analysis of imaging data (Li et al, 2011; Skup et al, 2012; Li et al, 2012; Polzehl et al, 2010), these methods are not computationally feasible even for thousands of SNPs. It is critically important to develop some novel methods to explicitly incorporate the spatial feature of the imaging data in FVGWAS, while achieving computational efficiency for ultra-high-resolution imaging and whole-genome sequencing.…”
Section: Conclusion and Discussionmentioning
confidence: 99%